The international movie industry - Kindem, Gorham Anders (Carbondale, Ill. : Southern Illinois University Press, 2000)
A comprehensive history of the international movie industry during the 20th century. Essays examine the film industries of 19 countries focusing on individual national movie industries' economic, social, aesthetic, technological and political/ideological development within an international context.
Japan / David Desser -- China / John A. Lent and Faye Zhengxing -- India / Radha Subramanyan -- Australia / Marcus Breen -- Israel / Owen Shapiro -- Iran / Hamid Naficy -- Senegal / Mathia Diawara -- South Africa / Arnold Shepperson and Keyan Tomaselli -- Hungary / Beverly James -- Soviet Union/Russia / Dmitry Shlapentokh -- France / Susan Hayward -- Germany / Marc Silberman -- Italy / Cristina Degli-Esposti Reinert -- Great Britain / Andrew Higson -- Sweden / Leif Furhammar -- Brazil / Randal Johnson -- Mexico / Joanne Hershfield -- Canada / Peter Morris -- United States / Gorham Kindem.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Motion picture industry -- History; Motion picture industry -- Economic aspects; Motion picture industry -- Social aspects; Cinéma -- Industrie -- Histoire; Cinéma -- Industrie -- Aspect économique.; Cinéma -- Industrie -- Aspect social; BUSINESS & ECONOMICS -- Industries -- Media & Communications; TECHNOLOGY & ENGINEERING -- Telecommunications; Motion picture industry; Motion picture industry -- Economic aspects; Motion picture industry -- Social aspects; Filmwirtschaft; Internationaler Vergleich; Filmindustrie; Economische aspecten; Sociale aspecten; History